Comparison of small incision lenticule extraction and transepithelial photorefractive keratectomy in terms of visual quality in myopia patients. Issue 8 (12th May 2021) - Lin, Meng; Zhou, Haitao; Hu, Zhongli; Huang, Jinhai; Lu, Fan; Hu, Liang
Abstract: Purpose: To comprehensively compare visual quality between small incision lenticule extraction (SMILE) and transepithelial photorefractive keratectomy (tPRK). Methods: Sixty‐four eyes in the SMILE group and 42 eyes in the tPRK group were enrolled in this study. In both groups, visual acuity, manifest refraction, higher‐order aberrations (HOAs), contrast sensitivity (CS) at four spatial frequencies (3, 6, 12, 18 c/d) under three conditions (photopic, low glare, high glare), the cut‐off value of the modulation transfer function (MTFcut‐off), the objective scatter index (OSI) and the Strehl ratio (SR) were measured preoperatively and 1, 3 and 6 months postoperatively. Results: At 6 months postoperatively, the SMILE and tPRK groups showed similar safety, efficacy and predictability. Additionally, MTFcut‐off, SR and OSI exhibited comparable results. In contrast, the photopic area under the logarithm of the CS function (AULCSF) showed better outcomes in the tPRK group than in the SMILE group (SMILE versus tPRK: 1.21 ± 0.10 versus 1.25 ± 0.09, p = 0.014). Furthermore, the induced coma aberrations were larger in the SMILE group (SMILE versus tPRK: 0.10 ± 0.16 versus 0.06 ± 0.12, 95% CI [0.08, 0.31], p < 0.0001). Conclusions: Both SMILE and tPRK obtained comparable visual quality at 6 months postoperatively, accompanied by better photopic CS and smaller induced coma aberrations with tPRK. Paying more attention to alignment or developing a centration technique would be beneficial for visual quality when performing SMILE.